Properties of medium density fiberboard (MDF) from sumble wood / Muhammad Hazwan Khalid - Khalid, Muhammad Hazwan (2021)
This is a study about utilization of fast-growing species in middle east region as a raw material to medium density fibreboard manufacturing. Currently in middle east region is having shortage of wood resource. Thus, plantation of fast growing species in middle east region is increase to meet the supply meet due to increase of demand of wood products from time to time. The purpose of this research is to seeking knowledge about the medium-density fibreboard using sumble wood species. The properties of medium density fibreboard had been determine which the MOR and IB shows no significant difference.